Green synthesized silver nanoparticles: Optimization, characterization, antimicrobial activity, and cytotoxicity study by hemolysis assay - Liaqat, Nida; Jahan, Nazish; Khalil-ur-Rahman,; Anwar, Tauseef; Qureshi, Huma (Frontiers in Chemistry, 2022)
Green nanotechnology has emerged as a viable option for the production of nanoparticles. The purpose of the current investigation was to synthesize silver nanoparticles (AgNPs) using Eucalyptus camaldulensis and Terminalia arjuna extracts, as well as their combinations, as green reducing and capping agents. The parameters (concentration of silver nitrate solution and plant extract, time, pH, and temperature) were optimized for maximal yields, regulated size, and stability of silver nanoparticles. The ultraviolet–visible spectrophotometer (UV-Vis) and the surface plasmon resonance band (SPR) were used to validate the synthesis of AgNPs. The size, shape, and stability of nanoparticles were assessed using a zeta analyzer and a scanning electron microscope (SEM). The biomolecules responsible for the reduction of silver ion (Ag+) and the stability of silver nanoparticles generated with the plant extracts were identified using Fourier-transform infrared spectroscopy (FTIR). The agar-well diffusion method was used to test the antimicrobial activity of biosynthesized nanoparticles against Bacillus subtilis, Staphylococcus aureus, Pasteurella multocida, and Escherichia coli. When 1 mM of silver nitrate (AgNO3) was added to plant extracts and incubated for 60 min at 75°C in a neutral medium, maximum nanoparticles were produced. Biosynthesized silver nanoparticles were stable, spherical, and monodispersed according to zeta potential and scanning electron microscopy. Silver nanoparticles synthesized with combination 2 and T. arjuna showed the highest zone of inhibition (16 mm) against B. subtilis while combination 3 showed the largest zone of inhibition against S. aureus (17 ± 0.8). It was concluded that greenly produced silver nanoparticles showed good antibacterial activity while causing negligible cytotoxicity.